2016
DOI: 10.1186/s13195-016-0189-7
|View full text |Cite
|
Sign up to set email alerts
|

Bapineuzumab for mild to moderate Alzheimer’s disease in two global, randomized, phase 3 trials

Abstract: BackgroundOur objective was to evaluate the efficacy (clinical and biomarker) and safety of intravenous bapineuzumab in patients with mild to moderate Alzheimer’s disease (AD).MethodsTwo of four phase 3, multicenter, randomized, double-blind, placebo-controlled, 18-month trials were conducted globally: one in apolipoprotein E ε4 carriers and another in noncarriers. Patients received bapineuzumab 0.5 mg/kg (both trials) or 1.0 mg/kg (noncarrier trial) or placebo every 13 weeks. Coprimary endpoints were change f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
169
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 244 publications
(176 citation statements)
references
References 12 publications
3
169
0
4
Order By: Relevance
“…Studies have tended not to highlight whether patients came alone or accompanied. For example, in the latest studies [22,23] on humanized monoclonal antibodies which failed to prove their effectiveness, this point did not appear, despite a very precise methodology. Likewise, numerous studies have highlighted factors associated with a faster rate of cognitive decline [24,25], but the modalities of the first consultation are also not clearly defined.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have tended not to highlight whether patients came alone or accompanied. For example, in the latest studies [22,23] on humanized monoclonal antibodies which failed to prove their effectiveness, this point did not appear, despite a very precise methodology. Likewise, numerous studies have highlighted factors associated with a faster rate of cognitive decline [24,25], but the modalities of the first consultation are also not clearly defined.…”
Section: Discussionmentioning
confidence: 99%
“…Another phase 1 clinical trial for immunotherapy targeting Aβ was completed with GSK933776 [30], but further clinical trials have not yet been started. Besides, AN1792 [31] and Bapimeuzumab [32], which were developed for immunotherapies to reduce Aβ, were tested in several clinical trials for AD patients, but all of them did not reach the primary endpoint or were ceased due to severe adverse effects. Several different drugs reducing Aβ with different mechanisms were also tried for the treatment of AD patients, but all of them unfortunately failed to show efficacy so far: namely, Tramiprosate (a small and orally-administered compound that binds to soluble Aβ and reduces amyloid aggregation and subsequent deposition) did not confirm any efficacy in a randomized, double-blind, placebo-controlled, multi-center study [33]; Tarenflurbil, a selective Aβ42-lowering agent, did not slow cognitive decline or the loss of activities of daily living in patients with mild AD in a phase 3 trial [34]; Semagacestat, a small-molecule-secretase inhibitor reducing Aβ, did not improve cognitive status and patients receiving the higher dose had significant worsening of functional ability [35]; Avagacestat, an arylsulfonamide-secretase inhibitor did not demonstrate efficacy and was associated with adverse doselimiting effects [36]; and intravenous immune globulin (IVIG) was reported not to show any efficacy in a phase 2 and 3 study evaluating safety and effectiveness of IVIG for the treatment of mild-to-moderate AD [37].…”
Section: Introductionmentioning
confidence: 99%
“…However, the lack of significant cognitive improvement in either group, together with the negative imaging outcomes, led to the discontinuation of this antibody [25]. Two additional trials with the same structure of ApoE 4 carriers and noncarriers were conducted in multiple countries with a similar lack of functional effectiveness, but without adverse effects [26]. Other studies have reported improved brain volume in imaging and plaque reduction in patients treated with bapineuzumab [27,28], but the relevance of these observations is not clear since functional studies have reported no significant benefits.…”
Section: First-generation Anti-aβ42 Antibodiesmentioning
confidence: 99%